2021
DOI: 10.1136/bmj.n28
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 has amplified moral distress in medicine

Abstract: Simply working harder cannot resolve the conflicts caused by responsibility without autonomy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 3 publications
1
64
0
4
Order By: Relevance
“…19 Experiences from previous pandemics confirm front-line healthcare professionals may develop poor mental health as a consequence, including formal mental health disorders such as post-traumatic stress disorder (PTSD) 17 and moral injury. 20 Moral injury refers to the moral distress caused by the powerlessness of healthcare professionals to meet patients' needs in a situation of high demand and constrained resources, and it has been linked with the development of suicidal thoughts, depression, anxiety, flashbacks or PTSD. 21 It is paramount that the importance of the impact on mental health and psychological well-being on all parts of the healthcare workforce is identified, characterised and addressed.…”
Section: Key Messagesmentioning
confidence: 99%
“…19 Experiences from previous pandemics confirm front-line healthcare professionals may develop poor mental health as a consequence, including formal mental health disorders such as post-traumatic stress disorder (PTSD) 17 and moral injury. 20 Moral injury refers to the moral distress caused by the powerlessness of healthcare professionals to meet patients' needs in a situation of high demand and constrained resources, and it has been linked with the development of suicidal thoughts, depression, anxiety, flashbacks or PTSD. 21 It is paramount that the importance of the impact on mental health and psychological well-being on all parts of the healthcare workforce is identified, characterised and addressed.…”
Section: Key Messagesmentioning
confidence: 99%
“…Doctors and nurses are exhausted or absent because of sickness or the need to self-isolate. Many will experience moral distress or its damaging sequel, moral injury, caused by the gap between what you think should be done for a patient and what can be done under constraints beyond your control 3. In the UK it may not yet, or ever, be about whether a patient can be ventilated.…”
mentioning
confidence: 99%
“…In terms of maternity care, this requires a sophisticated understanding of what 'companionship' means, over the whole life course, and for mother, baby, and family. It also requires attention to the potential moral distress of maternity care staff (and health care staff in general, including ultrasonographers) who are faced with the stress of having to balance these two imperatives with real people, in intensely emotional real time, repeatedly day in and day out, and at times with insufficient PPE equipment available; at a time when they, too could be pregnant women at risk of exposure to infection, or parents/carers fearful of infecting family members (25)(26)(27)(28). The study by Nguyen and colleagues identified that that infection risks for acquiring infection were high for staff compared to women, and particularly among front-line health-care workers (29).…”
Section: Discussionmentioning
confidence: 99%